2023
DOI: 10.1093/plcell/koad054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer activation via TCP and HD-ZIP and repression by Dof transcription factors mediate giant cell-specific expression

Abstract: Proper cell-type identity relies on highly coordinated regulation of gene expression. Regulatory elements such as enhancers can produce cell type-specific expression patterns, but the mechanisms underlying specificity are not well understood. We previously identified an enhancer region capable of driving specific expression in giant cells, which are large, highly endoreduplicated cells in the Arabidopsis thaliana sepal epidermis. In this study, we use the giant cell enhancer as a model to understand the regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We further tested whether, and to what extent, giant cells lose their identity and de-differentiate by examining the expression of molecular markers specific to giant and small cells ( 12 , 13 , 46 ). Live imaging of ATML1-OX inflorescences containing the giant and small cell markers treated with mock and 300 nM cafenstrole, revealed that in 300 nM cafenstrole, cells started to express the small cell marker basipetally from the sepal tip, compared with mock-treated sepals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further tested whether, and to what extent, giant cells lose their identity and de-differentiate by examining the expression of molecular markers specific to giant and small cells ( 12 , 13 , 46 ). Live imaging of ATML1-OX inflorescences containing the giant and small cell markers treated with mock and 300 nM cafenstrole, revealed that in 300 nM cafenstrole, cells started to express the small cell marker basipetally from the sepal tip, compared with mock-treated sepals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accession Col-0 was used as the wild type accession throughout the experiments, except for in comparison to the cer1-1 , cer3-1 , cer6-2 , and cer6-2R mutants which are in the Landsberg erecta (L er ) background. The small cell (CS70134) and giant cell markers (pAR111) were previously described ( 12 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Giant cells establish sepal curvature and are involved in plant defense ( Roeder et al 2012 ). In this issue of The Plant Cell , Lilan Hong, Byron Rusnak, Clint S. Ko, and colleagues ( Hong et al 2023 ) uncovered the regulatory mechanism driving cell-specific gene expression during giant cell formation in Arabidopsis sepals. In particular, they dissected the function of a 1 kilobase region previously shown to enhance gene expression in giant cells ( Roeder et al 2012 ).…”
mentioning
confidence: 99%